Study on Inlet and Engine Integrated Model with Normal Shock Position Feedback - Haoying Chen; Haibo Zhang; Zhihua Xi; Qiangang Zheng (International Journal of Aerospace Engineering)
In order to consider the inlet and engine integrated model of supersonic airliner, the dynamic identification and control of inlet normal shock are studied. The research is based on the bleed air flow rate under supersonic conditions. With the two-dimensional CFD model of supersonic inlet, the dynamic and static effects of the bleeding flow rate on the normal shock position were investigated. The transfer function was identified, and simultaneously the paper carried out a comprehensive study of inlet and engine integrated model, which is established based on the inlet shock position model and engine component level model. The relationship between normal shock position and total pressure recovery coefficient has been taken into consideration in this model. Based on the inlet and engine integrated model, the closed-loop control simulation of normal shock position is carried out. The results show that the model could resist the disturbance of the inlet flow and keep the inlet and engine matching operation point stable near the optimal value.